The boy who reached for the stars : a memoir - Morillo, Elio, 1993-; Molinari, Cecilia (HarperOne, an imprint of HarperCollinsPublishers, 2023)
"Elio Morillo's life is abruptly spun out of orbit when economic collapse and personal circumstances compel his mother to flee Ecuador for the United States in search of a better future for her son. His itinerant childhood sets into motion a migration that will ultimately carry Elio to the farthest expanse of human endeavor: space. Overcoming a history of systemic adversity and inequality in public education, Elio forged ahead on a journey as indebted to his galactic dreams as to a loving mother whose sacrifices safeguarded the ground beneath his feet. Today, Elio is helping drive human expansion into the solar system and promote the future of human innovation--from AI and robotics to space infrastructure and equitable access" --